Thermal aspects of the pairing correlations in finite nuclei - Civitarese, O.; Dussel, G. G.; Perazzo, R. P. J. (North Holland Publishin Co., 1983)
Fil: Civitarese, O. Universidad Nacional de La Plata; Argentina